CASE REPORT: SUSPECT HOG CHOLERA VIRUS INFECTION IN PIGLET AT BUAHAN VILLAGE, PAYANGAN DISTRICT, GIANYAR REGENCY, BALI - Indah Ihsan Wahyuni; Tri Komala Sari; I Made Kardena; I Nengah Kerta Besung; Ida Ayu Pasti Apsari (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Hog Cholera or Classical Swine Fever is a viral disease that attacks all ages of pigs. This viral disease is caused by the Hog Cholera virus from the genus Pestivirus, family Flaviviridae. The virulence of the Hog Cholera virus depends on the age and level of immunity of the pig. The case animal used was a 3 months old landrace pig, originating from one of the farms in Buahan Village, Payangan subdistrict, Gianyar district, Bali. The clinical symptoms that appeared in the case animals were yellowish-gray diarrhea, high fever, anorexia, cough, weakness, and erythema on the skin of the stomach and ear areas. Confirmation of the diagnosis of Hog Cholera virus infection is made from the results of changes in anatomical pathology and histopathological results. Anatomical pathological changes occur in almost all organs, and the changes that occur include hemorrhage and even congestion. The results of histopathological examination showed that in most of the organs that experienced changes, inflammatory cells were visible, which were dominated by mononuclear (lymphoid) cells. Based on the anamnesis, clinical signs, epidemiological signs, anatomical and histopathological changes observed, as well as qualitative fecal examination, it can be concluded that the pig case is suspected of being infected with the hog cholera virus and strongyl worm.